VD_FINDINFO AA 97/24 - 14/2025 vom 20. Januar 2025 - VD Tribunal cantonal (2025)
DÉCISION D'IRRECEVABILITÉ, EXPERTISE MÉDICALE, MOTIF DU RECOURS | 36 LPGA, 43 al. 1 LPGA, 43 al. 2 LPGA, 44 LPGA, 52 al. 1 LPGA, 7j al. 1 OPGA